Nurses' engagement with power, voice and politics amidst restructuring efforts. Issue 3 (16th February 2020) - McMillan, Kim; Perron, Amélie
Abstract: Change is inevitable, and increasingly rapid and continuous in healthcare as organizations strive to adapt, improve and innovate. Organizational change challenges healthcare providers because it restructures how and when patient care delivery is provided, changing ways in which nurses must carry out their work. The aim of this doctoral study was to explore frontline nurses' experiences of living with rapid and continuous organizational change. A critical hermeneutic approach was utilized. Participants described feeling voiceless, powerless and apolitical amidst rapid and continuous organizational changes which fuelled apathy, cynicism and disengagement from the organization. However, critical analysis of the data showed that nurses actively engaged with power, voice and politics through resistant and transgressive behaviours in micro‐ethical moments of practice. There is a need to reconceptualize the concepts of voice, power and politics in nursing as there is dissonance between nurses' beliefs about these concepts and what they are enacting in practice. Recognizing their enactment of power, voice and political agency at the micro‐level may empower nurses. Empowerment would mitigate the high levels of reports of powerlessness experienced in practice during organizational changes.